Multifocal Gastric Ulcers Caused by Diffuse Large B Cell Lymphoma in a Patient With Significant Weight Loss - Mark A. Gromski MD; Jennifer L. Peng MD; Jiehao Zhou MD, PhD; Howard C. Masuoka MD; Attaya Suvannasankha MD; Suthat Liangpunsakul MD (SAGE Publishing, 2016)
Primary gastrointestinal (GI) lymphoma is a heterogeneous disease with varied clinical presentations. The stomach is the most common GI site and accounts for 70% to 75% of GI lymphomas. We present a patient with gastric diffuse large B cell lymphoma (DLBCL) who presented with significant weight loss, early satiety, and multifocal ulcerated gastric lesions. Esophagoduodenoscopy should be performed in patients presenting with warning symptoms as in our case. Diagnosis is usually made by endoscopic biopsies. Multiple treatment modalities including surgery, radiotherapy, and chemotherapy have been used. Advancements in endoscopic and pathologic technology decrease turnaround time for diagnosis and treatment initiation, thus reducing the need for surgery. Health care providers should maintain a high level of suspicion and consider gastric DLBCL as part of the differential diagnosis, especially in those with warning symptoms such as weight loss and early satiety with abnormal endoscopic findings.